Analysis of the relationship between Tax Revenue and Government Expenditures in Indonesia - Muhammad Birrul Alim; Aulia Pamasa Setiyantono; Suci Nurul Zakiah (Journal of International Conference Proceedings, 2021)
In reality, government spending in emerging nations has been steadily increasing from time to time. Controlling it through fiscal policy, such as tax collections and government expenditure, is one of the measures that may be implemented. The primary goal of this study is to determine the magnitude of the link between tax income and government spending in Indonesia from 2000 to 2020. The World Development Index and the Central Bureau of Statistics are the primary data sources used by the researcher to attain this study goal. The researcher utilized the Vector autoregressive (VAR) technique and the Granger causality test to determine the link between tax income and government spending. Because the coefficient of determination is 65.41 percent, which is far from 100 percent, and the two variables, namely tax revenues and government expenditures, are not affected by the clause relationship, the results of this study indicate that the trend of the government expenditure ratio is less stable. The two variables do, however, have a short-term link, and there is no long-term balancing relationship between government spending and tax income.